Corporate Governance and Firm Value – An Empirical Study of Financial Services Firms in India - Negi, Gautam; Jain, Arpit (Indian Journal of Finance, 2022)
Empirical evidence on the association between firm value and corporate governance has mixed results depending on the chosen attributes for governance and firm value. The study investigated this relationship for financial services firms in India. Based on the literature review, four attributes of corporate governance were chosen: ownership concentration, institutional ownership, board independence, and CEO duality. Tobin’s Q value was taken as a proxy for firm value. The dataset consisted of 20 companies formin part of the National Stock Exchange financial services index. An additional two control variables are included in the model: the firm’s size and leverage ratio. All data were sourced from the annual reports of the companies, and the period of study is from 2016 – 2020. The panel data were analyzed using the generalized method of moments. The empirical findings revealed a positive and significant impact of ownership concentration, institutional ownership, and board independence on firm value, while the CEO duality role had no impact on firm value. The study contributed to the corporate governance literature of financial services firms in India.